A critical Review on dominant Vata dosh in Tridosh siddhant.: Array - Baronia, Chandrashri; Husain, Mariya; Raole, Vaidehi (Ayurline: International Journal of Research in Indian Medicine, 2019)
Vata dosha is important dosha in body. It is responsible for all types of movements in human body as well as all types of reflexes are carried out by Vata dosha. Vata dosha inside human body represents Vayu in external environment. Vata is the only moving dosha among the three and it carries Pitta and Kapha all over the body along with it. Now in this article we are going to study – Nirukti of Vata dosha, functions of Vata dosha, characteristics of Vata dosha, types and locations of Vata dosha and Importance of Vata dosha over Pitta and Kapha dosha.